2008
DOI: 10.1007/s11547-008-0320-3
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided percutaneous treatment of abdominal-pelvic abscesses: a 5-year experience

Abstract: Percutaneous drainage is feasible and effective in treating abdominal and pelvic abscesses. It may be considered both as a preparatory step for surgery and a valuable alternative to open surgery. Failure of the procedure does not, however, preclude a subsequent surgical operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
24
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 28 publications
8
24
0
1
Order By: Relevance
“…All abscesses with fistula to the genitourinary system were successfully treated, while 4 of 10 abscesses with fistula to the gastrointestinal system resulted in failure (40%). Our results confirm the results of other studies which had lower success rates with percutaneous drainage in the presence of enteric fistula (10,11,16,20,21). The time necessary to heal the enteric tear extends the duration of catheter use (11,20).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…All abscesses with fistula to the genitourinary system were successfully treated, while 4 of 10 abscesses with fistula to the gastrointestinal system resulted in failure (40%). Our results confirm the results of other studies which had lower success rates with percutaneous drainage in the presence of enteric fistula (10,11,16,20,21). The time necessary to heal the enteric tear extends the duration of catheter use (11,20).…”
Section: Discussionsupporting
confidence: 89%
“…According to published reports, minor complications such as bacteremia, and catheter-related problems, occur in around 3% of cases (1,10,11,21). In the present study, minor complications such as accidental catheter removal, obstruction and kink were observed in 6.7% of abscesses.…”
Section: Discussionsupporting
confidence: 59%
“…Observational studies from a number of centers have shown it to be a safe effective alternative to surgical intervention, with equivalent success rates, comparable mortality (10-20%) and morbidity (~25%) [14,15] . Inspite of the 100% technical success in the procedure , which is exactly the same as in Marianne E et al study [16], failure of drainage in our study occurred in 5 patients( 12.5%), compared to Kumar et al study [17] , in which 3% failed to improve and underwent operative intervention, and to Lagana et al 8.4 % [18]. Others reports include Haage et al with 14% [19], Lang et al with 23% [20], Jaques et al with 34% (15% failure and 18% partial success) [21].…”
Section: Discussionsupporting
confidence: 87%
“…Antibiyoterapinin tek başına yetersiz kaldığı ve drenaj tedavisinin uygulanmadığı durumlarda İAA'lar sepsise neden olabilmekte, %45-100 mortal seyretmektedir. Radyolojik görüntüleme yöntemleri eşliğinde perkütan apse drenajı minimal invaziv, kolay, efektif, güvenli ve tolere edilebilir olup, cerrahiye göre düşük mortalite ve morbidite oranlarına sahiptir [1][2][3][4] . Bu çalışmadaki amacımız, perkütan drenaj (PD) yöntemi uyguladığımız intraabdominal apse olgularında; kullandığımız tedavi yaklaşımı, seçilen yöntem ve araçlar ile tedaviden elde edilen sonuçların sunulmasıdır.…”
Section: Introductionunclassified